Unprovoked transformation of saddle back to coved ST-segment elevation ECG pattern - Firdaus, Muhammad; Ardian Rizal (Universitas Brawijaya, 2025)
Background Brugada syndrome (BrS) is a heritable arrhythmia that is clinically characterized by spontaneous coved ST segment elevation and a negative T wave in the right precordial lead. Some psychotropic medications, anesthetics, cocaine, excessive alcohol consumption, and fever have been identified as potential causes of VF and SCA in BrS. Case Illustration A 35-year-old man was hospitalized after experiencing unexplained syncope. It was felt 3 times within an hour and was preceded by lightheadedness, nausea, and vomiting. He did not experience palpitations, chest pain, or shortness of breath prior to the syncope. Prior to syncope, he had no history of fever, dehydration, drinking, or taking any medications. There was no family member died suddenly because of heart disease. The physical examination, CXR, laboratorium, and echocardiography were all within the normal range, but the electrocardiogram showed a coved ST segment elevation with an inverted T wave at V1-V2, as well as a saddle back ECG pattern two weeks later with a J point of 2 millimeters at V2. The combination of symptoms and ECG findings led to the BrS diagnosis. He underwent ICD implantation at RSUD Dr Saiful Anwar Malang for secondary prevention. After several months of ICD check-ups, there were no VT/VF events or ICD shock therapy. Conclusion A change in the ecg of the brugada pattern from type 2 to 1 is often accompanied by known ethiologies. But an unprovoked conversion of the BrS type is possible in rare cases.